Iranian Islamic Revolution and the Transformation of Islamist Discourse in Southern India: 1979–1992 - Thodika, Shaheen Kelachan (Religions, 2023)
By focusing on the publications of Jamaat-e-Islami Hind (JIH) in the Malayalam language, this article argues that the 1979 Iranian Islamic Revolution (IIR) marked a rupture from the disenchantments of the 1947 partition of British India and Cold War-centered politics for the Islamists of Kerala. This rupture from the colonial past and a Western-inspired intellectual climate had resonances in the discourse on Islam in Kerala. The Iranian revolution not only imported the idea of Islamism or revolution but also a renewed interest in democracy, modernity and the idea of “Islamist political” to the southwest coast of India. In an attempt to write an intellectual history of emotions related to the IIR, this paper argues that in the case of Islamists, there was a strong tendency to break from the intellectual discourse of the nation-state and begin afresh in politics, and the moment of 1979 provided what they sought for long.